Straw-based biochar mediated potassium availability and increased growth and yield of cotton (Gossypium hirsutum L.) - Muhammad Farooq Qayyum; Ghulam Haider; Muhammad Ali Raza; Abdel Kareem S.H. Mohamed; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni; Shafaqat Ali (Journal of Saudi Chemical Society, 2020)
Potassium (K) being the major limiting factor affecting cotton yield and quality has received massive research attention and the effects of various K fertilization techniques/organic amendments have been studied extensively. However, it is not clear whether the straw based, high pH biochar affects K availability, lint yield and quality of the cotton crop in alkaline calcareous soils. In the present study, we carried out a field experiment on a moderate to strongly calcareous silt loam soil to demonstrate the effect of straw-based biochar and potassium application levels on the growth, seed cotton yield and the lint quality. The experimental treatments comprised of two factors, A) biochar types i) Control no biochar, ii) Rice husk biochar (RHB), iii) Wheat straw biochar (WSB), and iv) Rice straw biochar (RSB), factor B) potassium application levels (i) control, no K fertilizer application, ii) K at 15 kg ha−1, and iii) K at 30 kg ha−1 (4 × 3 × 3, n = 36). Results showed that overall cotton growth and yield was significantly improved with increasing rates of potassium application. Three biochar sources affected seed cotton yield and quality with varying effects. For instance, the RSB increased plant height (11.71% to 22.47%), number of bolls per plant (0.74% to 13.75%), average boll weight (35.44% to 36.22%), the seed cotton yield was increased by 14.48% over the control when rice straw biochar was applied in combination with potassium at 30 kg ha−1. However, the ginning out turn (%) was declined with potassium application in combination with all three-biochar compared to control (no biochar addition). The WSB increased staple length and micronaire by 4.32% and 24.50% without potassium application. The potential effects of straw based biochar and potassium application on seed cotton yield and quality deserve further studies to identify the most suitable biochar as per soil chemical properties.